Addressing the Impact of Non-intrinsic Uncertainty Sources in the Stability Analysis of a High-Speed Jet - Granados-Ortiz, Francisco-Javier; Airiau, Christopher; Ortega-Casanova, Joaquín (Elsevier, 2021)
It is acknowledged by mechanical and aeronautical engineers that many important industrial fluid mechanics simulation-based decisions are made by analysing Reynolds-Averaged Navier-Stokes (RANS) simulations. However, despite that the use of RANS simulations has become a necessity, still unrealistic conditions such as not considering experimental variability or blindly trust a turbulence model happens in practice. This is an important concern in simulation of high-speed jet flows, as the reliability and the accuracy of RANS is still an issue. In this work non-intrusive Uncertainty Quantification (UQ) has been applied to the linear stability analysis of 3D RANS simulations of an under-expanded supersonic jet under uncertainty. The Parabolized Stability Equations (PSE) are utilised for the first time in the literature in a probabilistic approach for the propagation of uncertainty upon CFD simulations. As PSE does not include turbulence nor stagnation pressure as parameters in their mathematical formulation (named non-intrinsic parameters in this work), this framework enables a recommended practice to quantify the impact of uncertainty from earlier stages on the latter jet instability analysis.
Keywords: Mecánica de fluidos; Stability Analysis; Uncertainty Quantification; Fluid Mechanics; CFD; Under-expanded jet